Analisis Persebaran Penyakit Demam Berdarah Dengue (DBD) Di Kecamatan Ngemplak Kabupaten Boyolali Tahun 2013 - Anggraeni, Shinta, Drs. Priyono, M.Si, Dra. Umrotun, M.Si (2016)
Analitycal research of the Dengue Hemorrhagic Fever (DHF) spread disease in district Ngemplak Boyolali Regency 2013 is aim to 1) analyze the pattren of Dengue Hemorrhagic Fever (DHF) spread disease in Ngargorejo village, Sobokerto, Ngesrep, and Donohudan 2) analyze the factor that influence the spread of disease Dengue Hemorrhagic Fever (DHF) Ngargorejo village, Sobokerto, Ngesrep, and Donohudan. Research methods used in this research is a survey method, while the election of the regional research using the method of purposive sampling. For sampling a census method using the information obtained from all respondent as many as 33. Research analysis use analysis of nearest neighbour that aims to find out the pattern of the spread of the disease and the product moment correlation is used to find out the relationship factor to disease dengue fever. The data used in this research is primary and secondary, primary data the result of the interview with respondent, while secondary data i.e. population density. Results of the stated that in the area of research has pattern of sprawl clumped and uniform. The pattern of distribution is in the village of Ngargorejo clumped in with the values of the spread and pattern of distribution i.e. 0,48 uniform is in the village of Sobokerto, Ngesrep, and Donohudan with each value of distribution i.e, 1,90, 1,85, and 1,62. Factor that have a very strong relationship to disease Dengue Hemorrhagic fever (DHF) is the population density with the highest correlation 0.80. While the other factor have a correlation of low value i.e. the behavior with a value of r = 0.446, age has value r = 0.304, and environmental conditions with a value of r = 0.367. Keyword : Dengue Hemorrhagic Fever (DHF), Distribution pattern, Factor Affecting Distribution Pattern